Patriarchy and gender-inequitable attitudes as drivers of intimate partner violence against women in the central region of Ghana - Yandisa Sikweyiya; Adolphina Addoley Addo-Lartey; Deda Ogum Alangea; Phyllis Dako-Gyeke; Esnat D. Chirwa; Dorcas Coker-Appiah; Richard M. K. Adanu; Rachel Jewkes (BMC, 2020)
Abstract Background In order to reduce women's exposure to violence and develop culturally appropriate interventions, it is important to gain an understanding of how men who use violence rationalize it. The present study sought to explore the perspectives of men who had used violence on their female partners, specifically their views on intimate partner violence (IPV), gender norms, manhood, their gender attitudes and to understand how these may drive male perpetrated IPV against women in the Central Region of Ghana. Methods This was a qualitative study involving purposively sampled adult men who had participated in a household-based survey in selected districts in the Central Region of Ghana and who had self-reported perpetration of IPV in the past 12 months. In-depth interviews were conducted with 17 men. Results Data revealed how a range of social, cultural, and religious factors ̶ stemming from patriarchy ̶ combined to inform the construction of a traditional masculinity. These factors included the notion that decision-making in the home is a man's prerogative, there should be rigid and distinct gender roles, men's perceptions of owning female partners and having the right to have sex with them whenever they desire, and the notion that wife beating is legitimate discipline. Findings suggest that it was through performing, or aspiring to achieve, this form of masculinity that men used varying forms of violence against their female partners. Moreover, data show that the men's use of violence was a tactic for controlling women and emphasizing their authority and power over them. Conclusions Developers of interventions to prevent IPV need to recognize that there is a coherent configuration of aspirations, social norms and behaviours that is drawn on by some men to justify their use of IPV. Understanding the perspectives of men who have perpetrated IPV against women and their motivations for perpetration is essential for interventions to prevent IPV. This is discussed as drawing authority from 'tradition' and so engaging traditional and religious leaders, as well as men and women throughout the community, in activities to challenge this is likely to be particularly fruitful.